Prevalence and Effect of Cerebral Small Vessel Disease in Stroke Patients With Aspirin Treatment Failure–A Hospital-Based Stroke Secondary Prevention Registry - Chou, Ping-Song; Sung, Pi-Shan; Liu, Chi-Hung; Sung, Yueh-Feng; Tzeng, Ray-Chang; Yang, Chun-Pai; Lien, Chi-Hsun; Po, Helen L.; Ho, Shang-Chang; Tsai, Yi-Te; Chen, Tsang-Shan; Wu, Shey-Lin; et al. (Frontiers in Neurology, 2021)
Background: Breakthrough strokes during treatment with aspirin, termed clinical aspirin treatment failure (ATF), is common in clinical practice. The burden of cerebral small vessel disease (SVD) is associated with an increased recurrent ischemic stroke risk. However, the association between SVD and ATF remains unclear. This study investigated the prevalence and clinical characteristics of SVD in stroke patients with ATF. Methods: Data from a prospective, and multicenter stroke with ATF registry established in 2018 in Taiwan were used, and 300 patients who developed ischemic stroke concurrent with regular use of aspirin were enrolled. White matter lesions (WMLs) and cerebral microbleeds (CMBs) were identified using the Fazekas scale and Microbleed Anatomical Rating Scale, respectively. Demographic data, cardiovascular comorbidities, and index stroke characteristics of patients with different WML and CMB severities were compared. Logistic regression analyses were performed to explore the factors independently associated with outcomes after ATF. Results: The mean patient age was 69.5 ± 11.8 years, and 70.0% of patients were men. Among all patients, periventricular WML (PVWML), deep WML (DWML), and CMB prevalence was 93.3, 90.0, and 52.5%, respectively. Furthermore, 46.0% of the index strokes were small vessel occlusions. Severe PVWMLs and DWMLs were significantly associated with high CMB burdens. Patients with moderate-to-severe PVWMLs and DWMLs were significantly older and had higher cardiovascular comorbidity prevalence than did patients with no or mild WMLs. Moreover, patients with favorable outcomes exhibited significantly low prevalence of severe PVWMLs (p = 0.001) and DWMLs (p = 0.001). After logistic regression was applied, severe WMLs predicted less favorable outcomes independently, compared with those with no to moderate PVWMLs and DWMLs [odds ratio (OR), 0.47; 95% confidence interval (CI), 0.25–0.87 for severe PVWMLs; OR, 0.40; 95% CI, 0.21–0.79 for severe DWMLs]. Conclusions: SVD is common in stroke patients with ATF. PVWMLs and DWMLs are independently associated with functional outcomes in stroke patients with ATF. The burden of SVD should be considered in future antiplatelet strategies for stroke patients after ATF.